Multiple sclerosis in sibling pairs: an analysis of 250 families. Issue 6 (1st December 2001) - Chataway, J; Mander, A; Robertson, N; Sawcer, S; Deans, J; Fraser, M; Broadley, S; Clayton, D; Compston, A
Abstract : OBJECTIVES: To assess the potential contribution of genetic factors to clinical phenotype in multiple sclerosis. METHODS: Using a cohort of 262 pairs of coaffected siblings from 250 families with multiple sclerosis, intersibling concordance analysis was used to explore underlying genetic mechanisms in disease pathogenesis by assessing parameters of disease course, clinical presentation, age and year of onset, and measures of disability and handicap. RESULTS: Adjusted intraclass correlation coefficients were not significant for either age of onset or for year of first symptom. One third of sibling pairs were concordant for presenting symptom (81/262), a result that was non-significant. However, course type was identical in 50% of the sibling pairs (κ=0.17 (95% confidence interval (95% CI) 0.08 to 0.26)) indicating a significant result. Severity of the disease at assessment, using the Kurtzke and CAMBS scales, demonstrated that whereas there was no agreement for relapse rate in the previous year within the sibship, there was significant concordance for measures of disability (κ=0.11 (95% CI 0.04 to 0.19)), progression (κ=0.09 (95% CI 0.01 to 0.18)) and handicap (κ=0.08 (95% CI 0.02 to 0.14)). CONCLUSIONS: Within a sibship, the clinical presentation tends to be different. However, once established, concordance is more likely to be seen for the ultimate course, leading in the end to similar disability and handicap scores. These results are consistent with the hypothesis that genes influence both disease susceptibility and evolution in multiple sclerosis.